The Issuance of Land Certificates from an Electronic System - Anisya Nur Setyani; Dahniarti Hasana; Siti Ummu Adillah (Sultan Agung Notary Law Review, 2022)
The Minister of Agrarian and Spatial Planning (ATR) / National Land Agency (BPN) launched the Regulation Number 1 of 2021 concerning Electronic Certificates which states that electronic certificates will be issued through an electronic system in the form of an electronic document. The significant difference between analog certificates and electronic certificates is the physical form, type of information and also the method of securing it. This study aims to determine and analyze the process of the Ministry of Agrarian Spatial Planning/National Land Agency in issuing electronic-based land certificates, to find out and analyze legal protection for the people who own electronic certificates as authentic evidence, to find out and analyze the obstacles that arise in the issuance of electronic land certificates and the resolution of these obstacles. This study uses a sociological juridical approach with descriptive analytical research specifications, the types of data in this study are primary data, secondary data, and tertiary data. Based on the results of research and discussion that the Ministerial Regulation concerning electronic certificates states that all data, information and/or electronic documents will be stored in an electronic system database that creates legal certainty. But in this case, considering the theory of preventive legal protection which has the aim of preventing disputes. This Electronic Certificate puts a lot of concern in it regarding the possibility of disputes that will occur, so it still needs to be reconsidered regarding the refutation of the Regulation of the Minister of Agrarian and Spatial Planning (ATR) / National Land Agency (BPN) No. 1 of 2021 concerning Electronic Certificates.